Application of sewage sludge for cereal production in a Mediterranean environment (Lebanon) - Danny Romanos; Nabil Nemer; Yara Khairallah; Marie Therese Abi Saab (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Management of sewage sludge generated from wastewater treatment plants is a big challenge for its potential reusage in agriculture. Most of the Lebanese local sludge is discarded in the water or in landfills (most wastewater plants are partially functional). The objective of this research was to assess the effect of the application of different sewage sludge rates on the wheat production as an alternative of chemical fertilizer. Method Field trials were conducted, for one-year study, in IAAT village in the Bekaa valley-Lebanon. The considered treatments of 4, 8 and 16 kg.m-2 rates were compared to a control treatment. Physicochemical and microbiological analysis were performed on sludge and soil samples (pre cultivation and post-harvest). The harvested wheat was also analyzed for several parameters as mineral content. Results Results presented significant differences between control and treatments. pH values decreased with biosolids additions; organic matter rose in the amended soils, macronutrients levels increased. Heavy metals outcome increased significantly after amendment, microbiological analysis didn’t show any contamination by Salmonella, E.Coli, Staphylococcus Aureus and Helminth eggs. As for wheat plants' evaluation, fiber and protein contents presented an increase similar to nitrogen and phosphorus. Conclusion These results are a key component that identifies the role of biosolids as pH regulator and soil conditioner which improves the physicochemical properties of soil without any risk of microbiological contamination. These results are promising and they encourage the use of biosolids as agriculture amendment.